SOCIAL MEDIA VISIBILITY PLATFORM INSTAGRAM: INSTITUTIONAL AND INDIVIDUAL OWNERSHIP LQ45 FIRM 2022-2023 - Rahman, Faisal Riza; Prabowo, Janitra (Jurnal Ilmiah Fokus Ekonomi, Manajemen, Bisnis & Akuntansi (EMBA), 2024)
The purpose of this research is to examine the impact of the response of social media users to posting company Instagram accounts (likes and comments) on individual share ownership and institutional share ownership of LQ45 companies in Indonesia. The data collection method uses a purposive sampling technique. The number of samples in this study were 37 LQ45 companies for the period August 2022-January 2024 which were listed on the Indonesia Stock Exchange and had active Instagram accounts. Data processing uses SPSS 26 with multiple linear regression. The results show that the response of Instagram users is able to increase institutional share ownership and individual share ownership. The results of this research interpretation find the company's visibility among investors. Increasing company visibility on Instagram makes information more accessible, especially for individual and institutional investors, so they are interested in investing more in these companies. Keywords: Instagram; Ownership; Visibility; Liquidity; Social Media